2009
DOI: 10.1161/hypertensionaha.109.139279
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Case Definition to Define Hypertension Using Administrative Data

Abstract: Abstract-We validated the accuracy of case definitions for hypertension derived from administrative data across time periods (year 2001 versus 2004) and geographic regions using physician charts. Physician charts were randomly selected in rural and urban areas from Alberta and British Columbia, Canada, during years 2001 and 2004. Physician charts were linked with administrative data through unique personal health number. We reviewed charts of Ϸ50 randomly selected patients Ͼ35 years of age from each clinic wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
228
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 289 publications
(234 citation statements)
references
References 16 publications
3
228
0
1
Order By: Relevance
“…Diabetes and hypertension were identified from hospital discharge records and physicians' billing claims using validated algorithms. 17,18 Comorbid conditions were defined from physician claims and hospital admissions data using validated coding algorithms and the clinical modification of the International Classification of Diseases, 9th revision, and the International Classification of Diseases, 10th revision. 19 Health services data were captured for all residents of Alberta during the study period, regardless of movement within the province.…”
Section: Measurement Of Sociodemographic Variables and Comorbiditiesmentioning
confidence: 99%
“…Diabetes and hypertension were identified from hospital discharge records and physicians' billing claims using validated algorithms. 17,18 Comorbid conditions were defined from physician claims and hospital admissions data using validated coding algorithms and the clinical modification of the International Classification of Diseases, 9th revision, and the International Classification of Diseases, 10th revision. 19 Health services data were captured for all residents of Alberta during the study period, regardless of movement within the province.…”
Section: Measurement Of Sociodemographic Variables and Comorbiditiesmentioning
confidence: 99%
“…12, 15 We defined baseline use of medications as use of drugs prescribed concomitant with, or in the 120 days before, the index prescription of an ACE inhibitor or an angiotensin-receptor blocker.…”
Section: Definitions Of Exposuresmentioning
confidence: 99%
“…Although individuals responsible for ICD coding in the DAD receive standardized training in Canada (33), there may still be coding variations across provinces that could limit the generalizability of these findings. Previous studies have compared the validity of case identification using administrative data against chart review in the areas of hypertension and diabetes mellitus, and found that the sensitivity results (diabetes mellitus range 90.2-92.1%, hypertension range 74.0-76.0%) are not significantly different between 2 provinces (Alberta and British Columbia) (21,24).…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of OA case definition are not high; however, these are the standard algorithms accepted for administrative database OA research. Further, previous research in other chronic disease areas have determined the case definition with the highest validity to be 2 physician claims within 2 years, or 1 hospitalization, with a minimum of 3 or more years of data (21)(22)(23)(24). Our estimates include only individuals who have accessed health care services paid for by the provincial health care insurance plan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation